The effective and innovative ways of teaching English language - Yoqubjanova Diyora (Research Parks Publishing LLC, 2021)
This article is devoted to analyze the effective and innovative and also quite interesting ways of teaching foreign language, that is, have a great importance of IT in the learning process as well as in the process of raising motivation among students to a higher level. It also describes different methods of multimedia among which the outline of video lessons, role-playing a game lessons, project based-learning have the leading role.